PENERAPAN PROFILE MATCHING DALAM MENGANALISA LAPORAN KEUANGAN PERUSAHAAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Annafi Franz; Emil Riza Putra (RJABM (Research Journal of Accounting and Business Management), 2019)
Financial statements are an important instrument that is the duty of every company to publish them every year. The issuance of financial statements is useful for knowing the company's financial position. Especially companies that have gone public financial reports must be published publicly as a form of financial transparency to stakeholders. The issuance of these financial statements is useful for investors as consideration for investing in shares or withdrawing their shares in certain companies. Analyzing financial statements in general is done by ratio analysis, which is by looking at the company's financial ratios. But by adding the analysis method will enrich the results of the analysis of the company's financial statements. The addition of the analytical method is done by the profile matching method, which is to measure the ability of the company's financial ratios and rank them according to the company that has the best results.